Darkness is my only companion a Christian response to mental illness - Greene-McCreight, Kathryn, 1961- (Grand Rapids, MI Baker, 2006)
Includes bibliographical references.
Keywords: Mental illness -- religious aspect -- Christianity; Pastoral care of the mentally ill